1997
DOI: 10.1046/j.1365-2672.1997.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological approach to extracellular polysaccharide production by Lactobacillus rhamnosus strain C83

Abstract: L . G AM A R, K. B LO ND E AU AN D J. -M . SI MO N ET . 1997. Extracellular polysaccharide production was studied by growing strain C83 of Lactobacillus rhamnosus in a chemically defined medium containing various carbon sources (glucose, fructose, mannose or maltose) at different concentrations. Mannose or a combination of glucose¦fructose were by far the most efficient carbon sources. An optimization of growth medium composition led to an improvement in both growth and EPS production. When the strain was cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 2 publications
2
59
0
Order By: Relevance
“…The optimal conditions such as temperature (42°C) and pH (6.5) for the growth of S. thermophilus ST1 were favorable for its EPS production. However, there were also reports that optimal conditions for EPS production by some LAB strains were different from those for their optimal growth (13). A number of LAB strains were shown to produce more EPS at a lower temperature for their optimal growth (19).…”
Section: Effect Of Temperature On Eps Productionmentioning
confidence: 99%
“…The optimal conditions such as temperature (42°C) and pH (6.5) for the growth of S. thermophilus ST1 were favorable for its EPS production. However, there were also reports that optimal conditions for EPS production by some LAB strains were different from those for their optimal growth (13). A number of LAB strains were shown to produce more EPS at a lower temperature for their optimal growth (19).…”
Section: Effect Of Temperature On Eps Productionmentioning
confidence: 99%
“…bulgaricus, Lactobacillus helveticus, Lact. rhamnosus and Streptococcus thermophilus) LAB (Cerning 1990;Gamar et al 1997). It has been shown that Lactobacillus kefiranofaciens produces an EPS, named kefiran, that has the ability to lower blood glucose in mice (Maeda et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…bulgaricus, L. helveticus, and S. thermophilus) LAB (5). The EPS produced by Lactobacillus rhamnosus belong to third group (14). The sugar composition of the EPS produced by L. rhamnosus R studied in this work, as determined on the hydrolysate by high-pressure liquid chromatography (HPLC) and by gas chromatography of the alditol acetates, is the following: Rha, 4; Glc, 2; and Gal, 1 (M. R. Van Casteren, personal communication).…”
mentioning
confidence: 99%